One-dimensional model for the computation of unsteady salinity intrusion in a river - Diep, Nguyen Van; Dac, Nguyen Tat; Duyet, Tran Ngoc (Vietnam Journal of Mechanics, 1982)
The study is concerned with the development of a predictive, on – dimensional. Mathematical model for the salinity intrusion in a river. This is accomplished by means of simultaneous weighted implicit finite difference solutions to the salt balance equation and to the continuity and momentum equation which definite the tidal motion. It is shown that the boundary condition on salinity at downstream can be specified by using one condition during the flood tide and another condition during the ebb-tide. The resulting mathematical model, as solved by a finite-difference numerical technique can be used in a predictive manner for transient condition of downstream, surface elevation and time-varying fresh water discharges at upstream.